Technical and economic feasibility Analysis for a green coal production unit using millet, maize and cotton stalks in the far North Region, Cameroon - BOGWARBE, Emilienne; Nimpa Ngoufo, Abed; Tsapi Takua, Ulrich (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Green coal obtained by carbonizing agricultural residues and biodegradable household waste, is one of the innovative solutions currently being used in several countries to tackle deforestation. The aim of this work is to study the technical and economic feasibility for a green coal production Unit in the far North Region of Cameroun. The objectives are to assess the potential of agricultural residues in the locality, the efficiency of the carbonizer, the thermo-chemical characteristics of the green coal produced and its acceptability by users and the viability of the project. For this purpose, an assessment of the used agricultural residues potential was carried out by the mean of residues/products ratio, then the efficiency of the carbonizer was evaluated by calculations as well as the quality of the green charcoal by compared combustion tests conducted in a small-scale enterprise based in Maroua using a "1-barrel" carbonizer. The acceptability tests were made through survey and the Return on Investment (RI) was used as a parameter to evaluate the profitability of the green coal production unit. The results have shown that (i) the theoretical potential of sorghum/millet, maize and cotton stalks is estimated at 2,688,062.4 tons per year, (ii) the efficiency of the carbonizer varies between 22 and 25% depending of the raw material, (iii) Arabic gum is the binder that gives the best quality to the green charcoal, (iv) the green charcoal can very easily find a market. Nonetheless, the Return on Investment shows a deficit in the manufacturing of green coal. Ways for improvement have been proposed. These include the use of a "3-barrel" carbonizer and the rising of the green charcoal selling price to 500 FCFA.